Voltage profile improvement in unbalanced distribution grids by sequential quadratic programming - CEYLAN, OĞUZHAN (My University, 2023)
The implementation of renewable energy resources (RERs) such as photovoltaic (PV) units and wind turbines (WTs) has been intensively used on active distribution networks (ADNs) due to their significant environmental, technical, and economic benefits. However, their intermittent nature causes some fluctuations in the voltage profiles, which lead to increased losses in the system. This study presents sequential quadratic programming (SQP) optimization method to improve voltage profiles by optimizing tap changer positions and reactive power output of the inverter of a single PV unit. The proposed optimization is applied to the IEEE 34-bus unbalanced distribution test system to validate its performance. Optimum voltage profiles are compared with the base case conditions where there are no PV sources and voltage regulators. The results show that the SQP provides reliable voltage profile improvement for various operational conditions.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Computer Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; ENGINEERING; ENGINEERING, ELECTRICAL & ELECTRONIC; Bilgisayar Bilimi Uygulamaları; Fizik Bilimleri; Elektrik ve Elektronik Mühendisliği; Computer Science Applications; Physical Sciences; Electrical and Electronic Engineering; active distribution networks; Renewable energy resources; sequential quadratic programming; tap changers; voltage profiles